Physical activity detection in patients with intracardiac leadless pacemaker. (25th September 2018) - Bari, Zsolt; Vamos, Mate; Bogyi, Peter; Reynolds, Dwight; Sheldon, Todd; Fagan, Dedra H.; Duray, Gabor Zoltan
Abstract: Introduction: The Micra Transcatheter Pacing System provides a rate adaptive pacing using an individually programmable three‐axis accelerometer. We evaluated the short‐ and mid‐term performance of the Micra activity sensor by testing all three available activity vectors during the exercise tests. Methods and Results: Implantation and follow‐up data were prospectively collected from the patients undergoing Micra implantation at our institution. Patients underwent a 5‐minute exercise test for each vector at predischarge (initial testing) and at scheduled in‐office visits (repeat testing). On the basis of measurements of activity counts during the test, vectors were categorized to be adequate (excellent or acceptable) or poor. A total of 278 tests with 818 vector measurements were analyzed in 51 patients during follow‐up (median duration was 18 months). Initial testing revealed the adequate quality of the nominal Vector 1 in 74.5% of the patients. Upon repeated testing at subsequent in‐office visits, Vectors 1 and 3 were comparable (adequate quality in 64.7% vs 68.6% of the patients; P  = 0.65) but better compared with Vector 2 (51.0%; P  = 0.10 vs Vector 1, P  = 0.01 vs Vector 3). In a subgroup of 45 patients programmed to VVIR mode, Vector 1 was selected in 46.7% of the patients after the initial test (Vector 2, 8.9%; Vector 3, 44.4%). Vector change was performed in 10 patients (22.2%) following repeated tests within 3 months of postimplantation. Conclusion: The three‐axis accelerometer‐based rate adaptive pacing feature proved to be feasible after manual selection of an adequate activity vector. Vector testing in Micra patients with chronotropic incompetence appears to be beneficial compared with the use of nominal Vector 1.